2014
DOI: 10.3390/molecules190810845
|View full text |Cite
|
Sign up to set email alerts
|

Desorption of Water from Distinct Step Types on a Curved Silver Crystal

Abstract: Abstract:We have investigated the adsorption of H 2 O onto the A and B type steps on an Ag single crystal by temperature programmed desorption. For this study, we have used a curved crystal exposing a continuous range of surface structures ranging from [5(111) × (100)] via (111) to [5(111) × (110)]. LEED and STM studies verify that the curvature of our sample results predominantly from monoatomic steps. The sample thus provides a continuous array of step densities for both step types. Desorption probed by spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Results for the curved Ag(111) crystal have been published before, but were newly analysed from the raw data here for consistent comparison with the curved Ag(001) crystal, leading to new insights. 14…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results for the curved Ag(111) crystal have been published before, but were newly analysed from the raw data here for consistent comparison with the curved Ag(001) crystal, leading to new insights. 14…”
Section: Resultsmentioning
confidence: 99%
“…We have previously determined this dose to correspond to a surface coverage of 0.06-0.08 ML. 14 The higher background signal after the desorption peaks (in Fig. 3 and 4) is due to the long vacuum time constant of water in our apparatus.…”
Section: Surface Structure Investigationmentioning
confidence: 85%
See 1 more Smart Citation
“…Nonetheless, there are some other examples in the current literature. For example, water desorption on a curved Ag crystal was recently reported . Those authors observed a significant linear dependence of the desorption temperature on the step density of the surface.…”
Section: Surface Structure Spread Single Crystalsmentioning
confidence: 94%
“…Although the range of surface structures available on such a partial section is limited, such crystals have been employed successfully in standard UHV systems. 11,12 Generally, the direction of curvature is chosen such that the curvature results from atomically straight step edges. Dome-shaped crystals offer a continuous range of surface structures, including straight and kinked step edges.…”
Section: Introductionmentioning
confidence: 99%